2022
DOI: 10.3390/foods11060843
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Omega-3-Enriched Sheep Diet on the Microbiota and Chemical Composition of Kefalograviera Cheese

Abstract: Kefalograviera is a well-known hard Greek cheese. The aim of this study was to determine how milk produced from ewes fed omega-3-enriched diets could influence the microbiota as well as the chemical composition of Kefalograviera cheese. At the start of the trial, 30 dairy ewes (Lesvos and Chios crossbreed) were selected and fed a conventional diet, based on alfalfa hay, straw and concentrate feed that contained soybean meal for a period of thirty days. Then, for a period of sixty days the same ewes were fed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Some of them have identified representatives of Enterococcus, Lactobacillus, Streptococcus, Lactococcus, and Pediococcus. The present study found no pathogenic microorganisms, which confirmed the fondings reported by some authors [2,4,5,21,22]. Other authors [5] report on artisanal cheeses in which molds and yeasts have a higher availability in the ripening process due to the penetrating air in the vessel (Tulum).…”
Section: Results and Duscussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some of them have identified representatives of Enterococcus, Lactobacillus, Streptococcus, Lactococcus, and Pediococcus. The present study found no pathogenic microorganisms, which confirmed the fondings reported by some authors [2,4,5,21,22]. Other authors [5] report on artisanal cheeses in which molds and yeasts have a higher availability in the ripening process due to the penetrating air in the vessel (Tulum).…”
Section: Results and Duscussionsupporting
confidence: 91%
“…The short-chain fatty acids (C4:0 -C14:0) and those with C16:0 were synthesized due to fermentation processes in the rumen of animals [22]. At the same time, long-chain fatty acids (C18:0 -C22:0) were mainly synthesized from lipids, which were absorbed into the bloodstream through the small intestine.…”
Section: Results and Duscussionmentioning
confidence: 99%
“…bulgaricus ( p -value = 0.0198) with 100% similarity identified by EzBioCloud’s 16 S rRNA gene-based ID and OTU_21: Lactobacillus helveticus / crispatus / gallinarum ( p -value = 0.0202) with 99.1% similarity identified by EzBioCloud’s 16 S rRNA gene-based ID that decreased and increased in the experimental cheese samples, respectively ( Figure 5 ). In our previous study, the omega-3-enriched diet of dairy ewes influenced the lactobacilli population of the produced Kefalograviera [ 22 ]; however, different Lactobacillus species were affected, namely, Lb. rhamnosus , Lb.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, an omega-3 enriched diet in dairy ewes led to compositional differences in the microbiota determined by conventional microbiological methods and an increase in the omega-3 polyunsaturated fatty acids in the produced Kefalograviera [ 22 ]. However, culture-independent methods can provide a more in-depth understanding of the composition and the diet-induced changes in the Kefalograviera microbiota, while metabolomic analysis can provide information on the microbial metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial isolates’ identification was performed with the Bruker Microflex™ LT MALDI-TOF MS system (Bruker Daltonik GmbH, Bremen, Germany) according to the ethanol-formic acid extraction procedure, as previously described [ 38 , 39 ]. Acquisition and mass spectra analyses were performed by the MALDI Biotyper software package (MBT Compass version 4.1) and the reference database version (BDAL Rev.…”
Section: Methodsmentioning
confidence: 99%